2023
DOI: 10.1186/s13690-023-01040-3
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between psychosocial well-being and leisure time physical activity among 160.000 young Finnish men: a cross-sectional study during 2015–2021

Abstract: Evidence on the relationship between psychosocial well-being and physical activity (PA) is insufficient, especially in young adults between 18 and 29 years. Identifying protective factors for psychosocial well-being as well as factors that may promote PA behaviour in this specific age group is crucial.The aim of the present study was to explore the association between self-reported leisure time physical activity (LTPA) and a number of measures of psychosocial well-being in a large sample of Finnish young men. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…The present findings offer insights into the mixed results of previous studies on the association between physical activity and prosocial behaviour. [21][22][23][24][25][26] Our study revealed a positive correlation between physical activity and reciprocity as well as a negative correlation with trust. The results of reciprocity were in accordance with our a priori hypothesis, whereas those of trust were not.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…The present findings offer insights into the mixed results of previous studies on the association between physical activity and prosocial behaviour. [21][22][23][24][25][26] Our study revealed a positive correlation between physical activity and reciprocity as well as a negative correlation with trust. The results of reciprocity were in accordance with our a priori hypothesis, whereas those of trust were not.…”
Section: Discussionsupporting
confidence: 48%
“…Existing evidence on the relationship between physical activity and prosocial behaviour suggest both positive [21][22][23] and null or negligible associations. [24][25][26] Consequently, there is a lack of clear evidence showing the effect of physical activity on human prosocial behaviour.…”
mentioning
confidence: 99%
“…A recent study assessed the importance of maintaining a healthy lifestyle such as participating in physical activity, eating a healthy diet, etc., in reducing obesity and improving health conditions [ 4 ]. Individuals who maintain regular physical activity are found to have sustained happiness, self-esteem, and optimism as compared to those who do not exercise regularly [ 5 ]. Physical activity thus helps to build confidence, is seen as therapeutic intervention, and can certainly improve one’s health and well-being [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research focused on the adolescent population emphasizes a model of positive development, which seeks to identify, understand, and strengthen the factors that increase the capacity of adolescents to maintain and improve their health and wellbeing. While health is understood from the combination of social, physical, and mental domains (World Health Organization [WHO], 2006), the concept of wellbeing broadens its hedonic meaning to eudaimonic (Appelqvist-Schmidlechner et al, 2023;Maurer et al, 2023), in that it emphasizes the potential of the person to engage and fulfill oneself, as well as develop and find meaning in one's life (Ryan and Deci, 2001). Consequently, the approach centered on the vision of a passive adolescent with deficiencies or incapacities who needs protection from risk 10.3389/fpsyg.2023.1258748 behaviors (Lerner et al, 2009), has been overtaken by one that considers the adolescent as an active agent and values his or her potential (Seligman and Csikszentmihalyi, 2000;Gagné and Vansteenkiste, 2013).…”
Section: Introductionmentioning
confidence: 99%